ON THE ORIGINS OF RULE OF LAW AND THE META-PHYSICS OF INSTITUTIONS - Lorenzetto, Bruno (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2015)
The question concerning the origins or the beginning of the concepts is a philosophical problem that is located at the core of some of the most important reflections in our current time. In specific, the question about the origins of the state – the Rule of Law – is taken as the object of this reflection. It´s known that there is a wide range of answers given to it, mainly by the classical perspective of distinct authors that addressed the issue, in an effort to create theories that could shape an outlook to the social community and explain some important themes which structure the identity of a society, as such, the origins of sovereignty, the legitimacy of the representatives, the declarations of rights and the functioning of the institutions. The aim of the present paper is to show the mechanisms that work in the “underground” of these concepts or, how does the institutions use a meta-physical production of self-legitimating acts. Problems that can be seen in the “we” of term “We the people”, in the following terms: who is the “we” that precedes the “We the people”, or constitutes the “people”? The state is thought as being “always there”, even before the “we”? One can say that our forebears created the state but, when? And, where did came the power that legitimated our forebears? On the other hand, from where is originated the legitimacy of the Law? How to enforce the law, remembering that the Law is an authorized and justified force, a force that justifies itself. And, furthermore, the operation that creates the Law tend to be a coup de force, that no prior foundation could, by definition, guarantee, ensure or contradict. In sum, the search for the origins of the Rule of Law implies in putting in evidence the aporias that constitutes both the Law and Politics and, as a consequence, the uses that Law makes of politics to legitimate itself, and vice versa. Considering that both institutions bear a meta-physical structure of legitimation.